A new species of Elachistocleis (Anura: Microhylidae) from north-western Argentina - Pereyra, Laura C.; Akmentins, Mauricio S.; Laufer, Gabriel; Vaira, Marcos (Zootaxa, 2013)
Elachistocleis haroi sp. nov. is described from El Algarrobal, Jujuy province, north-western Argentina. The new species is diagnosed by the dorsal pattern of mid-longitudinal bright yellow stripe from the intraocular zone, surpassing the post-cephalic transverse skin fold, to vent; dorsum grayish brown mottled with a paravertebral symmetric pattern of dark spots resembling a pine tree; and a thin regular yellow line on the posterior surface of the thighs and tibiae. The advertisement call is a long trill with an average duration of 3.18 seconds, multipulsed with a mean dominant frequency of 4.56 kHz. The tadpole is characterized by the oral dermal flaps with papillae-like edges.